The use of English as a lingua franca in teaching a second language: Teachers’ perspectives: - Giannakou, Aretousa (Entrepalavras, 2024)
The present research explores the perspectives of primary education teachers on the use of English as a lingua franca in the second language classroom, in a context where English is spoken as a heritage language by migrant students. The study employed a qualitative research design, utilizing three distinct methods to explore the perspectives of twelve teachers: (a) a questionnaire; (b) written accounts; and (c) elicitation of metaphors. Non-English-speaking teachers were shown to be hesitant to adopt translanguaging practices in their teaching. However, the triangulation of results indicated a generally positive attitude toward using English in translanguaging, reinforcing its role in supporting the effective learning of young students with a migrant background. The study highlights the importance of training teachers so that they can appreciate the advantages of pedagogical translanguaging in the context of intercultural education involving students of migrant origin.